Naskah Kebijakan Penguatan dan Inovasi Pendidikan Tinggi Hindu: Rekomendasi Kebijakan untuk Modernisasi Kurikulum, Pelestarian Budaya dan Reformasi System Pendidikan - Ni Made Wiratini (Jurnal Penjaminan Mutu, 2025)
Hindu higher education in Indonesia plays an important role in maintaining cultural diversity and introducing spiritual values that can be adapted in the context of globalisation. However, the challenges of curriculum modernisation and cultural preservation are major issues in the development of Hindu higher education. This research aims to provide policy recommendations that can address these issues, focusing on three main aspects: curriculum modernisation, cultural preservation, and education system reform. Modernisation of the Hindu higher education curriculum needs to be done by integrating the latest science and technology, and adjusting to the needs of the labour market and social developments. In addition, the preservation of Hindu culture should be an integral part of the curriculum to ensure that students not only gain academic knowledge, but also a deep understanding of Hindu traditions and noble values. Reform of the higher education system needs to include improving the quality of teaching, facilities, and accessibility of education for all levels of society. These policy recommendations are expected to provide a solid foundation for Hindu higher education that is sustainable, inclusive, and relevant to the challenges of the times. Through a comprehensive and innovative approach, Hindu higher education can play a role in producing the next generation that is able to maintain cultural identity while adapting to global demands.